Functional Food Based on Potato - Xu J; Li Y; Kaur L; Singh J; Zeng F (MDPI (Basel, Switzerland), 2023)
Potato (Solanum tuberosum L.) has gradually become a stable food worldwide since it can be a practical nutritional supplement and antioxidant as well as an energy provider for human beings. Financially and nutritionally, the cultivation and utility of potatoes is worthy of attention from the world. Exploring the functionality and maximizing the utilization of its component parts as well as developing new products based on the potato is still an ongoing issue. To maximize the benefits of potato and induce new high-value products while avoiding unfavorable properties of the crop has been a growing trend in food and medical areas. This review intends to summarize the factors that influence changes in the key functional components of potatoes and to discuss the focus of referenced literature which may require further research efforts. Next, it summarizes the application of the latest commercial products and potential value of components existing in potato. In particular, there are several main tasks for future potato research: preparing starchy foods for special groups of people and developing fiber-rich products to supply dietary fiber intake, manufacturing bio-friendly and specific design films/coatings in the packaging industry, extracting bioactive proteins and potato protease inhibitors with high biological activity, and continuing to build and examine the health benefits of new commercial products based on potato protein. Notably, preservation methods play a key role in the phytochemical content left in foods, and potato performs superiorly to many common vegetables when meeting the demands of daily mineral intake and alleviating mineral deficiencies.
Keywords: antioxidants; cancer prevention; phytochemicals; potato protease inhibitors; starchy food